Preferensi Konsumen dan Faktor yang Mempengaruhi untuk Pembelian Gula Pasir Lokal dan Premium di Kota Palembang - Muhammad Aditya Rafli; Yunita Yunita (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2022)
The goals of this study are to: (1) describe the traits of consumers who purchase premium and local sugar in Palembang; (2) examine the variables that affect the demand for premium and local sugar in Palembang; and (3) look at the characteristics of consumer preferences when purchasing premium and local sugar in Palembang. Analysis of consumer satisfaction levels is done using preference theory. According to SNI sugar, premium sugar is the highest grade of sugar. When compared to SNI sugar, local sugar is of higher quality. Using a random sampling case study approach was the research methodology. This study, which was conducted in December 2021, included 23 consumers of local sugar and 31 consumers of premium sugar. Chi square analysis and a valid and reliable Likert scale were employed in this investigation. The findings revealed that the majority of premium sugar respondents in Diamond Supermarket were female, had four or fewer family members, were between the ages of 31 and 35, had an average monthly income of more than Rp3,000,000, were recent college graduates, and worked as various types of private employees. The dominant characteristic of rice respondents is in the Diamond supermarket where women who have <4 family members at the age of around 31-35 years, most of whom graduated, with an average income of < Rp2,500,000 / month. Factors affecting the demand for premium and local sugar in supermarkets are price, income, and gender, while family members do not influence demand. The most considered attribute in buying premium sugar and local sugar is the price.